Prehospital Reversal of Warfarin-Related Coagulopathy in Intracerebral Hemorrhage in a Mobile Stroke Treatment Unit. Issue 5 (May 2015) - Gomes, Joao A.; Ahrens, Christine L.; Hussain, Muhammad Shazam; Winners, Stacey; Rasmussen, Peter A.; Uchino, Ken
Abstract : Supplemental Digital Content is available in the text.